Intracurricular Learning of Religious Values and Children's Discipline in the Independent Curriculum in Kindergarten - Made Anggi Sasa Regita; Nice Maylani Asril; Dewa Gede Firstia Wirabrata (Jurnal Pendidikan Multikultural Indonesia, 2024)
Instilling good character values needs to be done from an early age as a foundation for children's personality development. However, the implementation of character education at the kindergarten level is currently not running optimally. Therefore, this study aims to analyze the influence of intracurricular learning on children's religious and discipline values within the context of the Merdeka Curriculum in kindergarten. This study employs an experimental research method using a one-group pretest-posttest design. The population consists of all kindergarten children, totaling 43 students. The research sample includes 21 students from class B2 and 22 students from class B3. The sample was selected using random sampling techniques. Data were collected through observation. The instruments for assessing religious and discipline values were observation sheets that had been validated by experts and tested for reliability. The collected data were analyzed in two stages: inferential statistics and prerequisite analysis using a t-test. The results showed that the significance value (2-tailed) was 0.411, which is greater than 0.05 (0.411 > 0.05). Based on these findings, it can be concluded that intracurricular learning has an effect on children's religious and discipline values in kindergarten. The implication of this research is expected to serve as a reference for teachers in conducting intracurricular learning.